Why regulate utilities? - Demsetz, Harold; Rodrigues Lanza, João Felipe (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The modern economic theory defines regulation as a necessary measure in utilities’ markets due to a supposed low compettitivity in those industries. Altough the regulatory methods which ar used in those industries have been consantly criticised for their inefficiency, th belief that the regulations are necessary has been kept unchanged. Therefore, the obective of this article is to prove that the convencional economic arguments that justify regulation in utilities are based on misled premises about these industries’ dynamics.